Smart Packgaes Box Berbasis Internet Of Things Menggunakan Telegram Bot - Sri Ayu Nur Hidayati Putri; Oktaf Brillian Kharisma; Harris Simaremare; Abdillah Abdillah (Universitas Budi Darma, 2023)
The trend of online shopping increases the use of delivery services. However, packages ordered online are often delivered when the customer is away from home, so the package is usually placed outside and unattended, which is not secure. Therefore, a safe place is needed to secure the package before received by the owner. Based on the problem, this study designed a Smart Packages Box based on the Internet of Things using the Telegram Bot, Wemos D1 R32 that connects the system with Telegram, Barcode Scanner GM66 to scan the barcode on the shipping label, Solenoid Door Lock, and ESP 32 Cam to monitor the condition of the package. Based on the Smart Packages Box test, the door lock can be opened if the barcode on the shipping label matches the receipt number that the owner has registered. The owner will get a notification status if the package has arrived through Telegram Bot. The barcode scan's response time test by courier was 3.20 to 4.50 seconds with a distance of 5 cm to 40 cm until the door locks open and locks again in 5 seconds. Based on the tests carried out there is a graph that illustrates a decrease at a distance of 50 cm which is caused by the distance being too far.The receipt number can be registered by writing